Uji Kemampuan Bangunan Pengaman Mengurangi Longsoran pada Balas Rel akibat Banjir - Atmojo, Pranoto Samto; Sachro, Sri Sangkawati; Budieny, Hary (MEDIA KOMUNIKASI TEKNIK SIPIL, 2013)
Ballast rail has a vital fuction to support the train’s load and its dynamic forces. This load is then distributed to the subgrade layer through pile of gravel under the ballast. Most of the design about the gravel layer (ballast) doesn’t take into account the effect of flood overflow on the rail, which is very likely to occur during rainy season. The Flood flows above the rail will reduce the ballast stability and then eroded. Part or most of the gravel were flushed out, thus resulting the ballast to be weak and may collapse, which is vey dangerous to the train traffic. Its therefore requires to investigate stability of the ballast under flood flow above the rail condition and any measure or improvement required by Hydraulic Modeling. The research is conducted at Hydraulic Laboratory, Diponegoro University. The model prototype is refer a tract rail at Mangkang-Semarang KM.12, with scale of 1:5. Its shown that the ballast  without a safety structure will start to scour when water level h1 = 15 cm , meanwhile with the structures Type 1 and Type 1 + 1 its start scour h1 = 17 and 19 cm respectively. The safety structure is able to scouring decrease , ie at the variation of h1 = 19 cm , there are 68.50 cm without structure, and with structure Type 1 and Type 2 are  29 and  26 cm respectively. This research shown that it needs to installing safety structure (sill) to reduce the danger cause of flood flow over the rail, especially at the flood prone area. The Management of train traffic could adopt this result how to protect of ballast scour cause of flood.